Effects of Nutrient Density and Photoperiod on the Performance and Abdominal Fat of Broilers - Oyedeji, J.O.; Atteh, J.O. (International Journal of Poultry Science, 2005)
The study investigated the effects of photoperiod and nutrient density on the performance and abdominal fat of broilers. Treatments consisted of a factorial arrangement of two diets containing 3200kcal/kg ME and 23% Protein and 2800kcal/kg ME and 18% Protein administered to broilers under either 12hour light per day, 8hour light per day or 6 hour light per day for 8 weeks. Results at market age showed that no significant interactions existed between nutrient density and photoperiod for feed intake, body weight gain and feed gain ratio (P > 0.05, P > 0.01). Also no significant interactions existed between factors for protein retention, fat utilization, available fibre, abdominal fat and cost to benefit ratio (P > 0.05, P > 0.01). Broilers subjected to low nutrient density diets experienced reduction in body weight gain and poorer feed to gain ratio (P < 0.05, P < 0.01). There was significant reduction in feed intake and abdominal fat of broilers exposed to only 6 hours of light per day as against the usual 12 hours of light per day (p < 0.05, p < 0.01). It was concluded that no meaningful interactions existed between nutrient density and photoperiod with respect to broilers performance. However, reducing photoperiod to 6 hours per day could be used as a tool for reducing abdominal fat hence, reducing sudden death syndrome and upgrading carcass quality of broilers.